Numerical simulation of cooling electronic components mounted in a vertical wall by natural convection. (7th April 2014) - Lahmer, Karim; Bessaïh, Rachid
<x content-type="archive" xml:space="preserve">Abstract</x> This paper is a numerical work to investigate thermal interactions between heat fluxes generated by electronic devices mounted on a vertical printed circuit board (PCB). In fact, the effect of some parameters such as Grashof number (Gr), the distance (S) between the heat sources and the upper exit distance (Le) was studied. The results show that a regular and uniform heat sources distribution in the inlet is very important in order to take advantage from the leading edge of the boundary layer and to obtain the necessary heat dissipation. The impact of parameters on the heat dissipation, characterized by the Nusselt number, has a different importance. For a Prandtl number Pr = 0.71, the (Gr) increases the heat exchange that is reflected by the increase of Nusselt number, and also participates to the formation of recirculation zones. The total Nusselt number Nu is increased when (Gr) is multiplied by 102. With regards to the distance (S) between the heat sources, the results show that Nu increases about 7% if the distance (S) doubles, and becomes approximately 17.8% when (S) quadruples. At the end, the heat transfer increases when increasing the distance (Le) of the upper exit length, especially on the second component. The total Nusselt number increases by 1.6% when (Le) increases by about 67%.